2021
DOI: 10.1016/j.heliyon.2021.e05939
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical contents, antioxidant activity and functional properties of Raphanus sativus L, Eruca sativa L. and Hibiscus sabdariffa L. growing in Ethiopia

Abstract: Information on phytochemical contents, antioxidant activity and functional properties of underutilized plants Figl (Raphanus sativus L.), Girgir (Eruca sativa L.) and Karkade (Hibiscus sabdariffa L.) grown in Benishangul Gumuz, Ethiopia are limited. In view of this, leaves and roots of Figl, leaves of Girgir, calyces and seeds of Karkade were evaluated following standard analytical methods. The total flavonoids, total anthocyanins, β-carotene and Lascorbic acid contents were ranged: 5.28-35.97, 0.01-2.53, 0.15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 45 publications
3
11
0
Order By: Relevance
“…The content of lutein in control rocket samples was 37.40 mg/100 g D.W., as shown in Figure 6. The β-carotene content was 36.31 ± 3.41 mg/100 g D.W., which is consistent with the findings of [49], who reported a β-carotene content of 36.00 ± 0.01 mg/100 g in dried rocket leaves. However, both β-carotene and lutein contents found in this study were higher than the values reported by previous studies [46][47][48].…”
Section: β-Carotene and Lutein Contentssupporting
confidence: 91%
See 1 more Smart Citation
“…The content of lutein in control rocket samples was 37.40 mg/100 g D.W., as shown in Figure 6. The β-carotene content was 36.31 ± 3.41 mg/100 g D.W., which is consistent with the findings of [49], who reported a β-carotene content of 36.00 ± 0.01 mg/100 g in dried rocket leaves. However, both β-carotene and lutein contents found in this study were higher than the values reported by previous studies [46][47][48].…”
Section: β-Carotene and Lutein Contentssupporting
confidence: 91%
“…Long-chain carotenoids are significantly more susceptible to oxidation and isomerization, which can happen during processing and storage [45]. Lutein and β-carotene have been reported to be the most abundant carotenoids in rocket leaves [46][47][48][49]. A higher content of β-carotene than that of lutein in both garden and wild rocket samples has been previously reported [46], however, lutein was reported at higher concentrations in rocket leaves [47,48].…”
Section: β-Carotene and Lutein Contentsmentioning
confidence: 98%
“…However, there was a significant (p < 0.05) difference in cabbage and tomatoes compared to Ethiopia kale. e moisture content of leafy cabbage (5.9%) and root carrot (13.39%) obtained in this study was similar to the results reported for gerger leaves (5.9%) and figl roots (2.9%) reported by Keyata et al [17]. e findings highlighted that relatively low moisture content recorded in the cabbage/ Brassica oleracea powders could stay in storage without deterioration for value addition.…”
Section: Proximate Composition and Gross Energy Contentssupporting
confidence: 89%
“…Clark 63K soybean variety (Forsido et al, 2019) and karkade seeds (Keyata et al, 2020) were used to enrich protein and fat contents. Figl leaves were chosen as premix due to high minerals content (Keyata et al, 2020) and β-carotene and L-ascorbic acid (Keyata et al, 2021a). The iodized salts and sugar were added as premixes in all formulated products to improve iodine supply and improve the taste of the complementary food.…”
Section: Experimental Materialsmentioning
confidence: 99%